Procedimientos a distancia. El Papel sellado en Chile, 1739-1786 : contingencias, tensiones y ajustes - Aude Argouse (Les Cahiers de Framespa)
Since 1640, the institution of rules for the distribution of stamped paper in Spanish America require a certain level of professionalism of the officials in charge of accounting. The progressive installation of distribution networks of this royal monopoly in the Kingdom of Chile outlines a geography of possibilities that legitimizes the distant action of those in charge. The spatial dimension of the proceedings and the level of instruction of the local officials responsible for collecting the tax show that they adapt to the pressures found on the ground. By examining the actions of a treasurer of stamped paper, Ignacio de los Olivos, this article analyses local practices in relation to this monopoly, in light of the intervention of Silvestre Garcia, the first accountant of the Royal Tribunal de Cuentas of Chile, in 1769. This article shows that, at least until the creation in 1786 of the Direccion General de Rentas Unidas, which merges the revenues of tobacco, playing cards, stamped paper and powder, the tax collection system implemented by Olivos remains in effect, in spite of the new accounting method carried out by Garcia.